Market perception of sovereign credit risk in the euro area during the financial crisis - Gonzalo Camba-Méndez; Dobromil Serwa (European Central Bank (ECB), 2014)
We study market perception of sovereign credit risk in the euro area during the financial crisis. In our analysis we use a parsimonious CDS pricing model to estimate the probability of default (PD) and the loss given default (LGD) as perceived by financial markets. We find that separate identification of PD and LGD appears empirically tractable for a number of euro area countries. In our empirical results the estimated LGDs perceived by financial markets stay comfortably below 40% in most of the samples. We also find that macroeconomic and institutional developments were only weakly correlated with the market perception of sovereign credit risk, whereas financial contagion appears to have exerted a non-negligible effect.
Keywords: C11; C32; G01; G12; G15; 330; CDS spreads; euro area; loss given default. ECB; probability of default; sovereign credit risk